2017
DOI: 10.3390/ijerph14111345
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Use in Students and Its Relation with Tobacco-Smoking: A Cross-Sectional Analysis of the i-Share Study

Abstract: While young adults often try e-cigarettes, little is known about its use and the reasons for experimentation, particularly in relation with tobacco-smoking. In 2016, data were collected from 2720 French-speaking students participating in a web-based study on students’ health: the internet-based Students Health Research Enterprise (i-Share) project. Univariate analyses and multivariable logistic regressions were performed to study the relationship between e-cigarette use and smoking status. Two out of five stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 38 publications
2
50
1
Order By: Relevance
“…Eleven papers studied young adults’ preference for flavor [ 11 , 19 , 21 , 22 , 34 , 35 , 38 , 42 , 51 , 69 , 70 ]. A study found that similar to adolescents, young adults also positively regarded e-cigarette flavor variety [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven papers studied young adults’ preference for flavor [ 11 , 19 , 21 , 22 , 34 , 35 , 38 , 42 , 51 , 69 , 70 ]. A study found that similar to adolescents, young adults also positively regarded e-cigarette flavor variety [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study found that similar to adolescents, young adults also positively regarded e-cigarette flavor variety [ 70 ]. French-speaking students also ranked flavors as the third most important reason for trying e-cigarettes, after curiosity and being offered by someone to try [ 38 ]. Furthermore, young adults seemed more likely to cite flavoring as a reason for use, especially compared with much older adults [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies conducted in the USA and internationally examined intention to try or initiation of e-cigarettes among adults. Two studies using convenience samples of young adults in Poland (n=46) and France (n=1086) both found that roughly 25%–30% of e-cigarette users tried or started using e-cigarettes because of the variability of flavours, though other reasons for initiation were rated more highly than flavours 56 57. Similarly, among an online convenience sample of international e-cigarette users (n=19 441) (note: study was funded by an e-cigarette advocacy group) and among a combined probability and non-probability sample of US adults (n=3878), the availability of appealing flavours was not frequently cited as a reason for e-cigarette initiation 58 59.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative nicotine metabolism in e-cig users and smokers deserves study. The behaviors repeatedly documented in this special issue [ 27 , 30 , 34 ] and previous work [ 40 , 41 , 42 ] cannot be explained by nicotine absorption alone, no matter how efficiently an e-cig aerosol delivers nicotine. Furthermore, the efficiency of current e-cig designs does not explain how older e-cigs changed conventional nicotine dependence measures.…”
Section: Discussionmentioning
confidence: 84%
“…Kinouani et al conducted a series of four online surveys of 2720 mostly French college students in the i-Share study, including 1305 (48%) smokers, at 6-month intervals [ 30 ]. Among 241 former smokers, e-cig past (146) and current (29) use was common.…”
Section: The Special Issuementioning
confidence: 99%